Rancang Bangun Sistem Pemipil Jagung Pada Sepeda Motor Listrik Roda Tiga - Lewi Lewi; Abdul Kadir Muhammad; Lifia Nur Ismayani; Akmal Setiawan (Politeknik Negeri Ujung Pandang, 2022)
Shelling is one of the post harvest handling for corn farmers where quality and time are important. Shelling that is done traditionally can cause fatigue and take a long time. The corn sheller machine on tricycle electric motorcycles can be used to save time during the shelling process. This research was conducted to design and make a corn sheller machine on a three-wheeled electric motorcycle that can be used to streamline time during the shelling process. In addition, the purpose of this research is to design and manufacture a corn sheller system on a three-wheeled electric motorcycle with a mechanical system with a DC electric motor as a driving force, separate corn kernels from the cob, and test with 1 kg of dry corn. The shelled corn kernels will be directly in the tub of a three-wheeled electric motorcycle while the cob will be thrown out. Based on the results of testing the corn sheller machine on a three-wheeled electric motorcycle, it was carried out twice, namely being able to shell 1 kg of corn with a percentage of crushed corn kernels of 25% for the first test and 35% for the second test.